Impact of n Sesamum roduction in Front line Demonstrations o P Panchmahal District of Gujarat - Rai, A. K.; Khajuria, S.; Lata, Kanak; Jadav, J. K.; Khadda, B. S.; kumar, Raj (Indian Journal of Extension Education, 2012)
Sesamum (Sesamum indicum L.) is one of the most important oilseed crops of the Panchmahal district of Gujarat.  However, its productivity in the district is very low. Attempts are being made to improve productivity and to increase area  under sesamum by adoption of HYVs (high yielding variety). In order to compare conventional sesamum with HYVs  varieties, 50 front line demonstrations (FLDs) were carried out in systematic manner on farmers' fields to show the worth  of new varieties in comparison to local check and thereby convincing farmers about potentialities of improved production  management practices of sesamum for further adoption, involving feasible and effective scientific package of practices.  The demonstrations clearly showed enhancement of productivity. At the same time area under sesamum cultivation was  also noticed to be enhanced. The yield was found to be increased from 369 kg/ha in local check to 470 kg/ha in FLDs.  Similarly, the cost : benefit ratio for HYVs varieties was found to be 1.65 as compared to 1.29 in local check. The  economic and cost : benefit ratio can be further improved to 1.68 by giving slightly higher inputs for cultivation and  marketing. The impact of FLDs was analysed which showed improvement of knowledge and satisfaction of farmers as the  main reason for mass scale adoption.
Keywords: Sesamum; production technology; front-line demonstration; adoption; benefit cost ratio